Adaptation of corporate management and human resource management in non–profit organizations - A. A. Gorsky (Путеводитель предпринимателя)
The socio–economic changes that societies have been experiencing in recent decades, caused by structural factors or specific circumstances, cause the emergence of problems, the solution of which the public sector, due to various circumstances, cannot fully provide. In these conditions, the activities of non–profit organizations — organizations of the third sector — require increasing efficiency and searching for the most effective mechanisms to ensure sustainable development and the achievement of social goals outlined in the mission of the organizations.Practice shows that there are serious differences in approaches to management in the corporate sector and the non–profit sphere. However, the methods of strategic management and human resource management characteristic of corporations can be adapted and successfully applied in the management of non–profit organizations. The paper concludes that in general, in order for these public organizations to be more effective in efforts to improve their management processes, they should focus on strategic management and human resource management tools.